The Differentiation Of Chromosomal Analysis By Karyotype And Fluorescent In Situ Hybridization (Fish) In The Product Of Conception (Poc) With Recurrent Pregnancy Loss (Rpl) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: About 1–2% of women experience recurrent pregnancy loss (RPL). Chromosome analysis is the current gold standard for genetic evaluation of products of conception (POC) but failure occurs in 10–40% of cases due to microbial contamination or lack of viable dividing cells. We implemented a reflex fluorescent in situ hybridization (FISH) assay to detect numeric chromosome abnormalities for unsuccessful culturesMaterials and Methods: All POC samples received in the laboratory were first processed for chromosome analysis (adherent cell cultured). To improve the success rate of POC analysis in our laboratory, we implemented a reflex FISH assay to detect common numeric chromosome abnormalities from unsuccessful cultures. On an unsuccessful chromosome analysis, an interphase FISH assay consisting of probes for chromosomes 13, 18, 21, X, and Y was performed on the uncultured fixed-cell pellet.Results: Out of 300 POC samples, chromosomal analysis results were obtained for 190 (63.3%) samples, 120 (63.2%) samples were found to have normal and 70 (37%) samples were found to have chromosomal abnormalities. Of the remaining failed 110 samples studied by FISH, an abnormality was identified in 30 (27.3%) samples. When the results for chromosome analysis and FISH were combined, an abnormality was detected in 100 of 300 (33.3%) analyzed samples. The most common chromosomal abnormality detected by FISH was Trisomy [Trisomy 13 (9, 9.7%), Trisomy18 (15, 16.1%), Trisomy 21 (29, 31.1%)] Monosomy X (10, 10.8%), and Kline filter syndrome - 47, XXY (5, 5.4%).Conclusions: Chromosomal investigation in POC using first conventional Karyotype and then FISH in resolving results have the advantage to reduce the failure rate of reporting chromosomal aberrations. We analyzed the prevalence of chromosomal abnormalities in POC involved in women with recurrent pregnancy loss.